The Electric Field and Ultrasonic Treatment Casing of Titanium Dioxide; Key Engineering Materials; Vol. 670 : Multifunctional Chemical Materials and Technologies - Smirnova V. V. Valentina Vladimirovna; Ilyin A. P. Aleksandr Petrovich; Brichkov A. S. Anton Sergeevich; Zabolotskaya A. V. Anastasiya Vladimirovna (2015, 2015)
Title screen